State and the peasantry Social and historical contestations over land use in rural Vietnam - Ariate, Maria Ima Carmela L.
Since early 2000, the Vietnamese government has embarked on a modernization plan that has entailed converting agricultural land for urban use. As Ha Noi expanded to include parts of neighboring provinces such as Hà Tây in 2008, thousands of peasants from Duong Noi faced state-sponsored land recovery spanning 197 hectares of agricultural land. Studies showed that law compensation for the peasants' right to use land is the major reason for their refusal to yield. The mourning tension between the authorities and the dan oan or hold-out peasants has led to a spike in hand-related protests and arrests from 2012 to 2015. At the forefront of these land-related protests were the dan oan of Duong Noi composed of 356 families who did not give in to the compensation offered, threats, and violence by the State in exchange for their land use rights. The research investigates their range of resistance from the times they were informed of the government's intention to recover their land use rights until 2015. Semi-structured interviews with the dan oan of Duong Noi and from other parts of Vietnam were carried out. Discourse analysis on news reports and official documents was also employed. Kerkvliet's 'everyday resistance', O'Brien's 'rightful resistance', White's definition of resistance as actions that aim to decisively change state policies, and Scott's 'moral economy of the peasant' serve as theoretical guideposts in data examination. I posit that the transformation from socialism to "market economy with socialist characteristics" has led to a fracturing of relations between the State and the peasantry, eventually putting both at odds with each other. While dan oan of Duong Noi have held on to their collective memory of their pivotal role in nation-building as a guarantee to social protection, it is the private business interests that held the favor of land tenure policies. This has implications on governance and democracy, pushing the enforcement of land recovery to its limits as it confronts more open and growing resistance. --Provided by the author.